Television Media Ownership as a Political Communication Tool in the Election - Pradita, Elfira; Indirwan, Indirwan; Ihsanudin, Muhammad (Law Research Review Quarterly, 2018)
Media as a pillar in democracy as well as a medium of public information has an influence on the formation of public opinion. In the context of elections, one of the media in political communication that has the greatest influence on voter choice is television. In principle, television media uses the frequency of society, then the public has the right to get balanced coverage. However, media owners who are part of electoral contestation use media as a communication media that abuses the media by broadcasting unequal news. The purpose of this study is to examine the use of television media as a means of political communication with media ownership, secondly, analyze various matters relating to television media ahead of the election. This research is a normative research that is based on basic and secondary materials, which are the rules and literature relevant to the object of research. Primary and secondary legal materials are obtained through library studies. The analysis used in this study is descriptive qualitative. The results showed that there was a linear relationship between media ownership of media owners in using their television media as a means of political communication. Regulations for using media in using media are used as personal communication tools in the Broadcasting Law, P3SPS, and General Election Commission Regulations. These regulations that maintain the media remain as a public information media that prioritizes the public and avoids various media in elections, although it is still needed for television media to remain neutral.